2021
DOI: 10.1007/s00035-021-00249-8
|View full text |Cite
|
Sign up to set email alerts
|

Flower preformation in the nival plant Ranunculus glacialis L.: shoot architecture and impact of the growing season length on floral morphogenesis and developmental dynamics

Abstract: Flower preformation is a widespread phenomenon in perennial plants from temperate and cold regions. An advanced preformation status reduces the prefloration period and thus increases the chance to mature seeds in time. Despite the particular importance of this strategy for high-mountain plants, studies are rare. Here we investigated how the length of the growing season impacts floral development, and to what extent floral development is synchronized with reproductive phenophases in the arctic-alpine species Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Based on a previous report [ 45 ], we selected four stages of underground flower development in E. japonicum , and samples from each stage were subjected to transcriptomic profiling. A similar approach for exploring transcriptomic profile for floral differentiation has been adopted in different species such as Ranunculus glacialis [ 60 ], Chrysanthemum morifolium [ 61 ], Chrysanthemum lavandulifolium [ 62 ], Staphisagria Ranunculaceae [ 63 ], rice [ 64 ], and Delphinieae [ 63 ]. The obtained results in this study suggested significant variation in the expression profiles at the different stages.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a previous report [ 45 ], we selected four stages of underground flower development in E. japonicum , and samples from each stage were subjected to transcriptomic profiling. A similar approach for exploring transcriptomic profile for floral differentiation has been adopted in different species such as Ranunculus glacialis [ 60 ], Chrysanthemum morifolium [ 61 ], Chrysanthemum lavandulifolium [ 62 ], Staphisagria Ranunculaceae [ 63 ], rice [ 64 ], and Delphinieae [ 63 ]. The obtained results in this study suggested significant variation in the expression profiles at the different stages.…”
Section: Discussionmentioning
confidence: 99%
“…In the Central European Alps, the species occurs from the subnival to the nival zone at sparsely vegetated sites with sufficient snow cover in winter [ 84 ]. The overwintering belowground rhizome system consists of individually rooted bud-like ramets (see Figure 10 A) with alternate arranged leaves and a uni- to multiflorous inflorescence [ 55 , 87 , 88 ]. Winter-dormant terminal flower buds are in an advanced development state [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…The overwintering belowground rhizome system consists of individually rooted bud-like ramets (see Figure 10 A) with alternate arranged leaves and a uni- to multiflorous inflorescence [ 55 , 87 , 88 ]. Winter-dormant terminal flower buds are in an advanced development state [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important trait ensuring longevity and thus surviving both seasonal climatic extremes as well as disturbances is the below-ground position of apical meristems as well as cohorts of preformed flowering buds (e.g., [6,20]). Below ground stems and buds, rather slow clonal spreading and massive belowground storage organs [21] together ensure that alpine plants are hardly affected by the year-to-year variation of weather conditions.…”
Section: Alpine Plant Life Strategiesmentioning
confidence: 99%